The Impact of the Learning Environment and Online Learning System using Google Meet on University Students' Motivation - Dony Martias; Nasrullah Djamil (AL-ISHLAH: Jurnal Pendidikan, 2023)
Students' motivation to learn has been impacted by the widespread changes to the school system and learning environment brought on by the COVID-19 pandemic. This research aimed to examine the impact of the learning environment and online learning system using Google Meet on accounting students' motivation at a state Islamic university in Riau during the COVID-19 pandemic. A survey approach was taken, with hypotheses tested and quantitative data used in this investigation. According to the findings of this study, the learning environment and online learning system using Google Meet positively impact students' learning motivation. This demonstrates that changes in the environment and learning system during the COVID-19 pandemic caused students to become more independent and critical thinkers.